2021
DOI: 10.33314/jnhrc.v18i4.2891
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Macrolide-Lincosamide-Streptogramin B Antibiotics Resistance Genes in Clinical Isolates of Staphylococci

Abstract: Background: Staphylococci are posing threat due to increasing trend of antimicrobial resistance particularly methicillin. Macrolide lincosamide streptogramin B (MLSB) family of antibiotics is commonly used to treat such infections. This study was aimed to determine the prevalence of inducible clindamycin resistance and observation of erm and msr genes among Staphylococci isolated from tertiary care hospital of Nepal during July 2017 to March 2018.Methods: Staphylococci from different clinical specimens were id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
2
2
1
Order By: Relevance
“…Out of 38 S. aureus , 67.5% were MDR, and 50% were MRSA. Similar findings were reported by studies in Nepal [ 21 , 23 ]. Higher percentages were reported by studies in Nepal [ 14 , 22 , 24 , 26 ] while lower percentages were reported by other studies in Nepal [ 20 , 25 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Out of 38 S. aureus , 67.5% were MDR, and 50% were MRSA. Similar findings were reported by studies in Nepal [ 21 , 23 ]. Higher percentages were reported by studies in Nepal [ 14 , 22 , 24 , 26 ] while lower percentages were reported by other studies in Nepal [ 20 , 25 ].…”
Section: Discussionsupporting
confidence: 92%
“…Also, 18.5% of S. aureus were MS phenotypes. Similar findings were reported by studies in Nepal [ 20 , 23 ] while higher percentages were reported by other studies in Nepal [ 23 , 26 ]. These variances in the reporting of MLSB resistance among S. aureus might be related to changes in circulating clones, as well as disparities in infection prevention measures and antibiotic prescribing trends in different hospital settings.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Clindamycin is used in soft tissue infections due to its efficacy against MRSA . Clindamycin is also a choice for outpatient treatment because of its cost, availability, and effectiveness against methicillin-resistant Staphylococcus aureus [ 78 , 79 ]. The combination with quinolones (e.g., ciprofloxacin) was frequently used.…”
Section: Discussionmentioning
confidence: 99%
“…Quite a number of studies on the impact of diverse classes of antibiotics in different animal models have been initiatedwith varied, wide-ranging and insightful outcome. Our test antibiotic (Clindamycin-hydrochloride) which is a lincosamide antibiotic has a wide spectrum of antibacterial activity including but not limited to, the management of septicemia; intra-abdominal, lower respiratory and gynecological infections; bone and skin related infections and a host of others (Al Khaja and Sequeira, 2021;Nagarkoti et al, 2021). It inhibits bacterial protein synthesis by preventing the formation of peptide bonds thus, exhibiting bacteriostatic or bacteriocidal activity depending on, the causative organism, location of infection and therapeutic dose (Park et al, 2019;Struzycka et al, 2019;Ma et al, 2019).…”
Section: Introductionmentioning
confidence: 99%